2010
DOI: 10.1002/ffj.2002
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Microbial transformation of isopinocampheol and caryophyllene oxide

Abstract: The biotransformation of (+)-isopinocampheol and (-)-isopinocampheol and (6R)-(-)-caryophyllene oxide was carried out by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Alpha-pinene contributes to the distinctive scent of fresh pine needles, conifers, and sage. It is also present in various herbs, including parsley, rosemary, basil, and dill, making it the most prevalent natural terpenes [ 138 ]. Studies have demonstrated its antioxidant activity [ 139 ] and anti-inflammatory effects in human chondrocytes [ 140 , 141 ], suggesting its potential for anti-osteoarthritic activity [ 141 ].…”
Section: Anti-neuroinflammatory Activity Of Phytochemicals In ...mentioning
confidence: 99%
“…Alpha-pinene contributes to the distinctive scent of fresh pine needles, conifers, and sage. It is also present in various herbs, including parsley, rosemary, basil, and dill, making it the most prevalent natural terpenes [ 138 ]. Studies have demonstrated its antioxidant activity [ 139 ] and anti-inflammatory effects in human chondrocytes [ 140 , 141 ], suggesting its potential for anti-osteoarthritic activity [ 141 ].…”
Section: Anti-neuroinflammatory Activity Of Phytochemicals In ...mentioning
confidence: 99%
“…Alpha-pinene contributes to the distinctive scent of fresh pine needles, conifers, and sage. It is also present in various herbs, including parsley, rosemary, basil, and dill, making it the most prevalent natural terpenes (Noma et al, 2010). Studies have demonstrated its antioxidant activity (Wang et al, 2008) and anti-inflammatory effects in human chondrocytes (Neves et al, 2010;Rufino et al, 2014), suggesting its potential for anti-osteoarthritic activity (Rufino et al, 2014).…”
Section: Terpenesmentioning
confidence: 99%